Perlindungan Hukum Terhadap Perempuan Korban Diskriminasi Berbasis Gender Di Lingkungan ASN Dari Kerangka Kilo 111 Dan Kilo 190 (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the implementation of legal protection for women victims of gender-based discrimination within the State Civil Apparatus and submissions to adopt the use of ILO Convention Framework 111 and ILO Convention 190. The formulation of the proposed problem is: How is the effectiveness of salatiga city government regulations and policies in preventing and overcoming gender discrimination experienced by female ASNs in salatiga city government work units and policies that should be taken by salatiga city government in preventing and tackling gender discrimination experienced by female asns. This research includes a typology of normative legal research supported by empirical data. Research data were collected through literature studies, document studies and interviews. The analysis of this study is carried out normatively empirically. The results of this study show that all policies related to Gender Mainstreaming are made for gender-responsive activities eliminate Employment and Job discrimination and violence and harassment in the w. Regarding the effectiveness of the regulations made by the Salatiga City Government, it has not been effective because there are still cases of discrimination and still tries to apply the regulations made to solve cases in Salatiga City. For policies that can further adopt ILO Convention 111 and ILO Convention 190 to implement rules that further orld of work. Of course, it is aligned with the hierarchy of regulations in Indonesia to be held in autonomous regions.